2020
DOI: 10.3390/agronomy10111719
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control and Soybean (Glycine max (L.) Merr) Response to Mixtures of a Blended Foliar Fertilizer and Postemergence Herbicides

Abstract: Growers commonly mix foliar fertilizers with postemergence (POST) herbicides to reduce application costs and/or to decrease soybean injury. Field studies conducted in 2015 and 2016 in Stoneville, MS, evaluated the impact on weed control and soybean (Glycine max (L.) Merr) injury, growth, and yield when combining a blended foliar fertilizer with POST herbicide applications. Herbicide treatments included no herbicide and glyphosate alone and in combination with S-metolachlor, fomesafen, or lactofen. The blended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Their application postemergence has been investigated with a view to prolonging the residual effect during the crop cycle. Selectivity is generally observed, with visible injury but minimal if any yield loss, and more consolidated results for smetolachlor (LAWRENCE et al, 2020;PRIESS et al, 2020). The present study demonstrated that applying s-metolachlor (up to 2,880 g ai ha -1 ) or clomazone (up to 1,800 g ai ha -1 ) does not compromise seed germination, even when used postemergence.…”
Section: Resultssupporting
confidence: 68%
“…Their application postemergence has been investigated with a view to prolonging the residual effect during the crop cycle. Selectivity is generally observed, with visible injury but minimal if any yield loss, and more consolidated results for smetolachlor (LAWRENCE et al, 2020;PRIESS et al, 2020). The present study demonstrated that applying s-metolachlor (up to 2,880 g ai ha -1 ) or clomazone (up to 1,800 g ai ha -1 ) does not compromise seed germination, even when used postemergence.…”
Section: Resultssupporting
confidence: 68%
“…This goal encourages the application of different strategies using an integrated weed managements approach. Farmers are used to mix POST herbicides with different mode of action and foliar fertilizers, in order to increase weed control and reduce soybean injury and application costs (Hydrick and Shaw, 1994;Lawrence et al, 2020). A potential strategy to mitigate the stress caused by the herbicides on the crop of interest may be represented by the use of biostimulant products.…”
Section: Introductionmentioning
confidence: 99%